The Role of Strategic Analysis in Building Intelligent Organizations: An Analytical Study of the Opinions of Managers of a Sample of Private Hospitals in the City of Erbil - ازان شريف أحمد; حکیم کریم هەلگورد (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
Objective: The current study aims to analyze the relationship and impact of the variable strategic analysis of the external and internal environments in private hospitals represented by their types (analysis of the external environment, analysis of the internal environment) in the dimensions of intelligent organizations represented by (strategic vision, common destiny, collective commitment, performance pressure, knowledge development, desire for change, regularity and compatibility). General Framework: The study completed its general framework by identifying the problem of the study by raising several questions focused on the nature of the relationship and the impact between the independent variable represented by the strategic analysis and the variable adopted represented by intelligent organizations, and a hypothetical plan was developed for the study consisting of four main hypotheses and in order to ascertain the validity of the hypotheses all underwent multiple tests and the study used the questionnaire form as a means of obtaining data. Study methodology: The researcher used the descriptive analytical approach, describing the main and sub-variables, as well as to analyze the relationships and influence between the variables of the study, namely strategic analysis and intelligent organizations. Study community and its sample: Represents the study community of private hospitals in Erbil city and numbered (24) hospitals. While the sample of the study was limited to (12) hospitals, and for the responding individuals, they numbered (102) members of the directors, department officials and units in the hospitals sample of the study. Hypotheses were tested through a range of statistical analyses and tests through the Statistical Analysis Programme (SPSS V.23). The most important conclusions and proposals of the study: The study reached a set of main conclusions and proposals, the most important of which revealed the results of the analysis of correlations about the existence of expellive moral relationships and a high level between strategic analysis and intelligent organizations at the macro and partial level where the strongest relationship between the analysis of the internal environment and intelligent organizations, Then came the relationship of analysis of the external environment and the variable adopted, which indicates that the more private hospitals researched towards the use of strategic analysis of these types, this has improved the capabilities of those private hospitals researched in the operations of intelligent organizations. The study suggests that private hospitals researched should study the components of social factors for the purpose of adapting to them by continuing to analyze the components of their external environment.